Service Quality and Customer Retention in Milky Way Restaurant - Reyes-Alzate, Corazon; Urbina, Marilou C.; Pendon III, Fernando T. (International Journal of Research in Interdisciplinary Studies, 2025)
This study examined the relationship between service quality and customer retention at Milky Way Restaurant using the SERVQUAL model. The primary objective was to assess how dimensions of service quality—tangibility, reliability, responsiveness, assurance, and empathy—influence customer retention factors such as frequency of visits, loyalty programs, and feedback and complaints. A descriptive-correlational research design with impact analysis was employed. Data were collected from 150 loyal customers using a structured questionnaire and analyzed through weighted mean, Pearson correlation, and regression analysis. Findings revealed that all five dimensions of service quality received a “Very Satisfied” rating, with reliability scoring the highest. Similarly, customer retention showed strong indicators, particularly in the areas of loyalty and feedback response. The study established a statistically significant relationship between perceived service quality and customer retention. Furthermore, regression analysis confirmed that service quality had a significant positive impact on customer retention. The study concludes that high service quality leads to increased customer retention in the restaurant industry. It recommends continuous training for staff, improvement in physical ambiance, and the implementation of well-structured loyalty programs. These enhancements can boost customer satisfaction and ensure long-term business growth. The findings serve as a basis for a proposed action plan to sustain and improve both service quality and customer loyalty.